2022
DOI: 10.1039/d2cc02412h
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric assembly of pyrazole and 1,2,3-triazole with a methylene bridge: regioisomerism and energetic properties

Abstract: An asymmetric N-bridged strategy was employed to link two different energetic building blocks. The resulting compounds not only exhibit good crystal density and low sensitivity, but also demonstrate the key...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…The synthesis routes of compounds DMPT are shown in Scheme 3 . Compound 1-(chloromethyl)-3,5-dinitro-1 H -pyrazol-4-amine ( CDPA ) was prepared according to similar procedures in the literature [ 28 ]. The reaction of intermediate CDPA , 5-aminotetrazoles, KOH and KI at 80 °C in acetonitrile for 12 h, subjected to silica gel column chromatography, gave rise to two methylene-bridged isomers 1-((4-amino-3,5-dinitro-1 H -pyrazol-1-yl)methyl)-1 H -tetrazol-5-amine ( DMPT-1 ) and 2-((4-amino-3,5-dinitro-1 H -pyrazol-1-yl)methyl)-2 H -tetrazol-5-amine ( DMPT-2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis routes of compounds DMPT are shown in Scheme 3 . Compound 1-(chloromethyl)-3,5-dinitro-1 H -pyrazol-4-amine ( CDPA ) was prepared according to similar procedures in the literature [ 28 ]. The reaction of intermediate CDPA , 5-aminotetrazoles, KOH and KI at 80 °C in acetonitrile for 12 h, subjected to silica gel column chromatography, gave rise to two methylene-bridged isomers 1-((4-amino-3,5-dinitro-1 H -pyrazol-1-yl)methyl)-1 H -tetrazol-5-amine ( DMPT-1 ) and 2-((4-amino-3,5-dinitro-1 H -pyrazol-1-yl)methyl)-2 H -tetrazol-5-amine ( DMPT-2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the energy performance of the compounds could be enhanced by introducing modification groups. Among all the five-membered azole rings, the pyrazole ring has more modification sites and better thermal stability compared to the triazole and tetrazole rings. , Thus, the introduction of modification groups on the pyrazole ring can be used to achieve energetic compounds with good stability while taking into account the energy properties.…”
Section: Introductionmentioning
confidence: 99%
“…The critical role of positional isomerism is documented in nearly all other areas of the chemical enterprise . For example, in the field of medicine, the isomers maybe have similar pharmacological effects but different potencies or have distinct pharmacological mechanisms of action (Figure A). Similarly, in the field of energetic materials, previous studies have shown that the arrangement of functional groups in isomers has a significant impact on physicochemical properties, including density, decomposition temperature, sensitivity, and so on. For example, the isomer 1,5-diamino-2,4,6,8-tetranitronaphthalene (DATNN-1) has a high density, while the isomer 2,7-diamino-1,3,6,8-tetranitronaphthalene (DATNN-2) has high thermostability (Figure B). Therefore, it is very important and meaningful to study the positional isomers, which could help to understand the structure–property relationships and to accelerate the development of new materials.…”
Section: Introductionmentioning
confidence: 99%